Additional External Costs Analysis and Environmental CBA - Dimitrijevic, Zinaida; Salihbegovic, Iris (Journal of Technology Innovations in Renewable Energy, 2017)
The sustainable development requires policies and measures which negative impacts would not be spilled over on another area or has trends that pose severe or irreversible threats to future quality of life. The environmental costs-benefits analysis (CBA) as well as multi criteria analyse are the most common used methods for the decision making processes including the approved methodology for quantifying external costs especially regarding air quality. Since the reducing one type of external cost generates another external cost due to fact that the problem is only shifted from the one area to the another CBA is not enough for the decision making process because external cost of a future implemented measure isn’t considered. By the usage of Life-cycle costing (LCC), a tool which evaluates the costs of an new installed asset imposed trough the adopted policy or measure throughout its life cycle, it is possible beside the common costs for conducting CBA include also the end-of-life and disposal costs as the new installed asset’s external costs too. These costs have to be calculated and added to the cost side of CBA before comparing to the benefits. So, for the purpose of decision making process of the retrofitting existing thermal power plants with DeSOx such calculation has been done as a case study for one thermal power plant in Bosnia and Herzegovina highlighting overall costs and benefits of the DeSOx installation.